ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ТЕКСТ ҲӘМ ОНЫҢ ТҮРЛЕРИ - Досжанова, Г.Д.; Усенова, Қ. (FAN va JAMIYAT, 2019)
The article is devoted to the types of texts in the Karakalpak language. It gives some statements about the volume structure, stylistic peculiarities and plot of the text. According to the extent the text is divided into maximal and minimal. According to the structure the texts may be stable and free. The author of the article analyzed the texts of the narrative, didactic, descriptive, emotional content, and also texts-decrees.